Examination of social disconnectedness and perceived social isolation on health and life satisfaction in community-dwelling adults with dysvascular lower limb loss. Issue 2 (14th April 2022) - Hitzig, Sander L.; Dilkas, Steven; Payne, Michael W.; MacKay, Crystal; Viana, Ricardo; Devlin, Michael; Cimino, Stephanie R.; Guilcher, Sara J.T.; Mayo, Amanda L.
Abstract : Background: People with physical disabilities are at risk for social isolation, which has been shown to negatively influence health and well-being. Objective(s): The purpose of this study was to examine the association of social disconnectedness and perceived social isolation (PSI) on health-related quality of life (HrQoL) and life satisfaction in adults with dysvascular lower extremity amputation (LEA). Study Design: Cross-sectional survey. Methods: Data were collected from community-dwelling adults with dysvascular major LEA (N = 231). The main outcome measures were the Short-Form 36 and the Life Satisfaction-11. Other measures were used to quantify comorbidities/secondary health conditions, PSI, social disconnectedness, self-efficacy, social support, and social engagement. Three hierarchical regression models were conducted to predict (1) physical HrQoL, (2) mental HrQoL, and (3) life satisfaction. Results: Approximately one-third of the sample had high levels of social disconnectedness and PSI. The regression model predicting physical HrQoL accounted for 47% of the variance and only found that higher levels of mobility, lower perceived impact of comorbidities/conditions, and higher levels of social engagement and self-efficacy were associated with better physical HrQoL. A model predicting mental HrQoL accounted for 36% of the variance, with older age, lower PSI, and higher levels of self-efficacy being significant predictors. Finally, the model predicting life satisfaction accounted for 56% of the variance, with older age, lower perceived impact of comorbidities/conditions, and higher self-efficacy remaining as significant predictors. Conclusions: These findings highlight that one-third of our sample were at risk for being socially isolated and that PSI was influential on mental HrQoL and life satisfaction. There is a need for approaches to address social isolation for people with dysvascular LEA living in the community to optimize their long-term health and well-being.